(untitled) (Research, Society and Development, 2022)
When pairs of liquid chemical species are mixed, biphasic regions may appear in the system instead of a monophasic region. When these phases are in equilibrium, it tells you which system is in liquid-liquid equilibrium. This phenomenon has great relevance in the industrial environment and in unit operations, such as liquid-liquid extraction. In this work, the thermodynamic modeling of a ternary system composed of water + acetic acid + ethyl acetate was carried out at two temperatures, 10 and 30ºC. The thermodynamic consistency of the experimental data was verified from the correlations of Othmer-Tobias and Hand, obtaining a correlation coefficient greater than 0.99, showing good consistency. The solvent extraction capacity (ethyl acetate) to separate the solute (acetic acid) was evaluated from the distribution coefficient and the separation factor. Thermodynamic modeling was used to predict the liquid-liquid equilibrium from the Non-Random Two-Liquids (NRTL) models and the Universal Quasi-Chemical (UNIQUAC) method using the gamma-gamma approach to compare with the results obtained experimentally. The global mean deviations were 1.63% and 2.39 for the UNIQUAC and NRTL models respectively, thus showing that they are effective in predicting the liquid-liquid equilibrium.